A surface enhanced Raman scattering nanotag library based on cucurbit[7]uril controlled nanoparticle aggregates for fast cell imaging - Zhu, Yuanshuai; Li, Xiaobo; Maknitikul, Sitang; Bileckaja, Narina; Peng, Qiyun; Gracie, Jennifer; Drabwell, Owen; Li, Sixuan; Glidle, Andrew; Dobson, Phil; Yuan, Xiaofei; Yang, Zhugen; et al. (Elsevier, 2026)
Surface Enhanced Raman Spectroscopy (SERS) nanotags offer ultrahigh sensitivity and multiplexing capability over and above traditional fluorescence dyes for bioimaging but suffer from more drawbacks of more complex synthesis and measurement. Here we report a facile method to create libraries of nanotags with diverse Raman reporters for sensitive SERS labelling, whilst addressing complexity and reproducibility of synthesis that many nanotags suffer from. We create and demonstrate a library of SERS nanotags synthesized via incorporation of different thiolated and non-thiolated Raman reporters (including barcoded combinations) into silver nanoparticle (Ag NP) aggregates, mediated by water soluble cucurbit[7]uril (CB7) as a molecular glue. These controlled aggregates achieve significant SERS enhancement regardless of whether the Raman reporter possesses functional groups for metal adsorption, greatly increasing the choice of potential Raman reporters for creating libraries of SERS nanotags with massive barcoding and multiplexing depth. Further coating of the SERS nanotag aggregates with functional polyethylene glycols results in long-term stability, excellent biocompatibility, and versatile functionality to attach biomolecules. We demonstrate the utility of our SERS nanotags in fast imaging of cell-particle interactions and multiplexed (‘multicolor’) surface biomarker mapping at 10 ms per point using a 1.5 mW laser or less. Our method is not only simple to implement but offers flexible and reproducible libraries of SERS nanotags with great potential for a broad range of biological labelling challenges requiring sensitivity, speed and multiplexing.
Keywords: 4018 Nanotechnology; Biomedical Imaging; Bioengineering; Biotechnology; Workforce Diversity and Outreach; Nanotechnology; Generic health relevance; Chemical Physics; 34 Chemical sciences; 40 Engineering; 51 Physical sciences